Malignant hyperthermia in a 6-month-old infant - P R Mathur; M Rundla; N Jain; V Mathur (Saudi Journal of Anaesthesia, 2016)
Malignant hyperthermia (MH) is a rare hypermetabolic disorder of skeletal muscles that manifests as a life-threatening crisis in susceptible individuals, after exposure to triggering agents, most commonly halothane and succinylcholine. MH presents with multiple nonspecific signs and laboratory findings such as tachycardia, hyperthermia, hypercarbia, acidosis, and muscle rigidity. Caffeine halothane contracture test is not available at most centers in India. Larach et al. have described a clinical grading scale for determining the MH raw score based on clinical findings and biochemical tests. The high degree of suspicion, early recognition and aggressive treatment should commence immediately. It is imperative to avoid triggering agents, such as volatile anesthetics and succinylcholine, and promote the use of total intravenous anesthesia in MH susceptible patients. We report a case of 6-month-old child undergoing laparotomy under general anesthesia, who presented with signs and symptoms of MH, had MH rank 5 and raw score 36.